2024
DOI: 10.1093/jb/mvae009
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the NLRP3 inflammasome inhibits stress granule assembly by multiple mechanisms

Daisuke Yoshioka,
Takanori Nakamura,
Yuji Kubota
et al.

Abstract: Proper regulation of cellular response to environmental stress is crucial for maintaining biological homeostasis and is achieved by the balance between cell death processes, such as the formation of the pyroptosis-inducing NLRP3 inflammasome, and pro-survival processes, such as stress granule (SG) assembly. However, the functional interplay between these two stress-responsive organelles remains elusive. Here, we identified DHX33, a viral RNA sensor for the NLRP3 inflammasome, as a SG component, and the SG-nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Poly-IC is a double-stranded homopolymer used as a model RNA that activate TRIF-dependent toll-like receptor-3 (TLR3) ligand, triggering intrinsic viral response pathways and the formation of SGs [20,21]. As expected, G3BP1 stained SGs were not present in untreated cells (Fig.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Poly-IC is a double-stranded homopolymer used as a model RNA that activate TRIF-dependent toll-like receptor-3 (TLR3) ligand, triggering intrinsic viral response pathways and the formation of SGs [20,21]. As expected, G3BP1 stained SGs were not present in untreated cells (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…A recent LC-Ms/Ms based study suggested CCDC124 protein as an interaction partner of a number of SG-localized protein including the well known SG marker protein G3BP1 [17]; and the data sets presented in https://doi.org/10.7910/DVN/EFBRHN), we decided inquire a possible colocalization of CCDC124 with G3BP1 at SGs. It was previously shown that a viral stress mimicking agent, poly-IC, induced activation of G3BP1 and the formation of cytoplasmic SGs [21]. We have analyzed SG localization of CCDC124 in U2OS cells expressing GFP11-tagged versions of this protein in a stable fashion (GFP11x 4 ::CCDC124, or CCDC124::GFP11x 4 ) in response to poly-IC treatments (Fig.…”
Section: Discussionmentioning
confidence: 99%